2017
DOI: 10.1371/journal.pone.0179822
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase inhibitor attenuates ischemia-reperfusion induced acute lung injury

Abstract: Ischemia-reperfusion (IR)-induced acute lung injury (ALI) is implicated in several clinical conditions including lung transplantation, cardiopulmonary bypass surgery, re-expansion of collapsed lung from pneumothorax or pleural effusion and etc. IR-induced ALI remains a challenge in the current treatment. Carbonic anhydrase has important physiological function and influences on transport of CO2. Some investigators suggest that CO2 influences lung injury. Therefore, carbonic anhydrase should have the role in ALI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This is problematic, as significantly higher IL-8 levels may result in higher mortality rates following lung transplantation ( 42 ). Lan et al ( 39 ) and de Perrot et al ( 40 ) reported that elevated TNF-α and IL-6 levels contributed to organ IR injury. In the present study, the results of ELISA demonstrated that IL-6, IL-8 and TNF-α levels were markedly increased in A549 cells following H/R induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is problematic, as significantly higher IL-8 levels may result in higher mortality rates following lung transplantation ( 42 ). Lan et al ( 39 ) and de Perrot et al ( 40 ) reported that elevated TNF-α and IL-6 levels contributed to organ IR injury. In the present study, the results of ELISA demonstrated that IL-6, IL-8 and TNF-α levels were markedly increased in A549 cells following H/R induction.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation serves an important role in the mechanism of LIRI ( 38 ), such that the regulation of inflammation has been revealed to effectively alleviate the disease ( 39 ). Previous studies have verified that IL-8 levels are markedly increased in lung tissue and systemic circulation after IR ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…CAs are metalloenzymes that catalyze the hydration of carbon dioxide to bicarbonate and protons ( Supuran, 2011 ). Studies have found that the inhibition of CA2 and CA4 in the proximal convoluted tubule could reduce bicarbonate reabsorption and causes metabolic acidosis, thereby would leading to the suppression of pro-inflammatory activation ( Hudalla, et al, 2019 ; Lan, et al, 2017 ). CA inhibitors can be a base of anti-infectives ( Supuran, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several promising avenues of research are emerging from the study of hibernating species [87], such as the use of H 2 S [88]. Other concepts include: the replacement of damaged mitochondria with healthy mitochondria at the onset of reperfusion by auto-transplantation in the heart [89]; the control of pH regulation through inhibition of carbonic anhydrase in lung transplantation, which impacts both pCO 2 levels, and Na-K-ATPase expression [90]; the sensitization of calcium channels in human hepatocytes for liver transplantation [91]; or the control of systemic iron load to protect against renal ischemia-reperfusion injury-associated sterile inflammation [92]. Finally, other drugs were recently studied: pharmacologic targeting of DHPS by N1-guanyl-1,7-diaminoheptane (GC7) or RNA interference–mediated inhibition of DHPS or DOHH induced tolerance to anoxia in immortalized mouse renal proximal cells [93].…”
Section: Additives In Preservation Solution: Improve the Now Whilementioning
confidence: 99%